Training farmers to tackle Newcastle Disease - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Mr. Demba Touray of The Gambia?s Department of Livestock Services describes the work of the department to control Newcastle disease.